Allergic contact dermatitis of both eyes caused by alcaftadine 0.25%: a case report - Kim, Jae Hyuk (BMC Ophthalmol, 2019)
BACKGROUND: To report the first case of allergic contact dermatitis (ACD) associated with alcaftadine 0.25% ophthalmic solution. CASE PRESENTATION: The patient was a 51-year-old woman with no previous history of side effects to ophthalmic antihistamine agents. She had been prescribed alcaftadine 0.25% for allergic conjunctivitis. On first application of the medication, she did not experience any cutaneous reaction. One day later, after the second alcaftadine 0.25% application, both eyelids became swollen, and erythematous changes were evident. On slit-lamp examination, conjunctival injection was noted in the absence of conjunctival swelling or any other findings. Fundus examination was unremarkable. To evaluate the cause of ACD, a patch test was performed and 48 h later was noted to be positive for alcaftadine 0.25%. Based on the positive patch test, the patient was diagnosed with ACD caused by alcaftadine 0.25%. After 9 days of treatment, the swelling and erythema completely resolved. CONCLUSIONS: Although there have been no previous reports of alcaftadine 0.25%-associated ACD, it should be suspected in patients with swelling and erythematous change of both eyes after using alcaftadine 0.25%.